Experimental Investigation of Particle Crushing Behavior of Melamchi Sand Using Compression Testing Machine - Adhikari, Binod; Acharya, Indra Prasad (Journal of Engineering Technology and Planning, 2025)
Understanding the particle crushing behavior of sand under high compressive stress is critical for accurate prediction of soil compressibility and strength characteristics. This study examines the particle breakage characteristics of Melamchi river sand under extreme vertical loads using a Compression Testing Machine (CTM). Dry sand specimens were placed in a CTM machine and loaded step-by-step upto 1000 kN (about 53 MPa). Particle size distribution analysis was done before and after each test to find D10, D20, D50, D60 and coefficient of uniformity (Cu) . Breakage indices were calculated to quantify the degree of particle breakage. Results show upto 59% reduction in mean particle size with increasing stress levels at 1000 kN. The findings confirm that grain crushing must be considered in geotechnical infrastructure works like deep pile foundations, rockfill dams, embankments and hydropower tunnels, where high stresses occur. The findings are useful for the design of gravel drains and soil filters, where stress-induced particle crushing can change gradation and influence filtration performance.